On the minimum limit to thermal conductivity of multi-atom component crystalline solid solutions based on impurity mass scattering. (September 2017) - Giri, Ashutosh; Braun, Jeffrey L.; Rost, Christina M.; Hopkins, Patrick E.
Abstract: We investigate the effect of mass disorder on the thermal conductivity of Lennard-Jones based multi-component solid solutions via classical molecular dynamics simulations. In agreement with Klemens' perturbation theory, the thermal conductivity reduction due to mass scattering alone is found to reach a critical point, whereby adding more impurity atoms in the solid solution does not reduce the thermal conductivity. A further decrease in thermal conductivity requires a change in local strain-field, which together with mass defect scattering can lead to ultralow thermal conductivities in solid solutions, surpassing the theoretical minimum limits of the corresponding amorphous phases. Graphical Abstract: